Urothelial cancer: a narrative review of the role of novel immunotherapeutic agents with particular reference to the management of non‐muscle‐invasive disease. (22nd January 2019) - Doyle, Emma; Crew, Jeremy; Mostafid, Hugh; Tuthill, Mark; Cerundolo, Vincenzo; Gerristen, Winald; Protheroe, Andrew
Abstract : Aim: This narrative review describes current guidelines for treating NMIBC, provides an overview of the principle behind immune checkpoint inhibition, and summarizes current evidence for checkpoint inhibitors in urothelial malignancy. Further, we discuss potential strategies for immune checkpoint inhibition in the management of NMIBC. Background: Adjuvant intravesical BCG immunotherapy has been the mainstay of treatment for high‐risk non‐muscle‐invasive bladder cancer (NMIBC) for decades but is associated with both a significant side effect profile and failure rate. Recently, a substantial body of trial data has been published demonstrating the successful use of systemic immunotherapy in the treatment of advanced urothelial malignancy and, in particular, a class of drugs known as 'immune checkpoint inhibitors'. This has led to the approval of a number of these drugs by the UK National Institute of Health and Care Excellence and the US Food and Drug Administration, and ongoing trials are examining use in the management of NMIBC. Methods: To identify relevant published data, using the PubMed/ Medline search engine, an online search of the Pubmed/ Medline archives was conducted using the terms bladder cancer' in combination with 'checkpoint inhibitors', and limited to articles in English published between 1966 and September 2017.To identify ongoing trials of interest but not yet published, a further search of the clinical trials.gov search engine was conducted using the term 'non‐muscle‐invasive bladder cancer'. Conclusion: There has been little advance in available adjuvant therapy for NMIBC treated with TURBT. Current intravesical therapies are associated with a high recurrence rate and significant side effect profile. The impending publication of the wealth of ongoing trials, both into the delivery and efficacy of checkpoint inhibition will direct the future treatment of NMIBC.